Pengaruh Strategi Segmenting Targeting Positioning Terhadap Keputusan Pembelian Pada Toko Baju Di PTM Bengkulu - Ratnawili Ratnawili; Desti Febrianty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of the Segmenting Targeting Positioning Strategy on Clothing Purchase Decisions for Clothing Store Consumers at PTM Bengkulu. This research method uses a quantitative approach, the object of research is 160 respondents at the Clothing Store Consumers at PTM Bengkulu. In this study, researchers used data collection methods by means of observation, interviews and distributing questionnaires. Multiple linear regression analysis, coefficient of determination, and also hypothesis testing. The results of this test can be seen from the multiple linear analysis test using SPSS, namely, Y = 11.495 + 0.261 (X1) + 0.328 (X2) + 0.457 (X3). From the results of the hypothesis test, segmenting has a positive and significant effect on the decision to buy clothes at PTM Bengkulu because the value of tsig < (0.019 <0.05) with a positive value of 0.261. Targeting has a positive and significant effect on the decision to buy clothes at PTM Bengkulu because the value of tsig < (0.030 <0.05) with a positive value of 0.328. Positioning has a positive and significant effect on the decision to buy clothes at PTM Bengkulu because the value of tsig < (0.000 <0.05) with a positive value of 0.457. Segmenting, Targeting, and Positioning have a significant effect on the decision to buy clothes at PTM Bengkulu because the value of Fsig = 0.00 <0.05 means Ho is rejected and Ha is accepted. This means that together Segmenting (X1), Targeting (X2), and Positioning (X3) have a significant effect on the decision to purchase clothes at PTM Bengkulu.